Barriers and pathways to environmental surveillance of antibiotic resistance in middle- and low-income settings: a qualitative exploratory key expert study - Ann-Christin Peters; D. G. Joakim Larsson; Ramanan Laxminarayan; Christian Munthe (Global Health Action)
Background Local and global surveillance of antibiotic resistance (ABR) has proven a challenge to implement effectively in low- and middleincome (LMI) settings. Environmental surveillance solutions are increasingly highlighted as a strategy to help overcome such problems, and thus to promote global health as well as the local management of ABR in LMI countries. While technical and scientific aspects of such solutions are being probed continuously, no study has investigated their practical feasibility. Objective Explore practical barriers for environmental surveillance of ABR in LMI countries, and pathways for surveillance experts to manage these. Methods To start charting this unknown territory, we conducted an explorative, qualitative interview study with key informants, applying a constructivist grounded theory approach to analyze the results. Results Barriers were identified across infrastructural, institutional and social dimensions, and pathways to manage them were mostly counterproductive from an ABR management perspective, including avoiding entire regions, applying substandard methods and failing to include local collaborators. Conclusion The research community as well as international agencies, organizations and states have key roles and responsibilities for improving the prospects of feasible environmental ABR surveillance in LMI-settings.